Investigation of repeated dose (90 day) oral toxicity, reproductive/developmental toxicity and mutagenic potential of ‘Calebin A’ - Muhammed Majeed; Kalyanam Nagabhushanam; Sankaran Natarajan; Sarang Bani; Anjali Pandey; Suresh Kumar Karri (Toxicology Reports, 2015)
The present work investigated repeated dose and reproductive toxicity of Calebin A in Wistar rats. A study for assessing the mutagenic potential of Calebin A through an AMES test is also described. Calebin A was orally administered to groups of 10 male and/or 10 female Wistar rats each, assigned to three dose levels (20, 50 and 100 mg/kg/body weight) once daily for 90 consecutive days. None of the animals in any of the treatment/control groups exhibited any abnormal clinical signs/behavioral changes, reproductive as well as developmental parameters, or gross and microscopic changes in both male and female rats. Calebin A was also evaluated for its ability to induce reverse mutations at selected loci of Salmonella typhimurium in the presence and absence of Aroclor 1254 induced rat liver S9 cell lines. In conclusion, 100 mg/kg/d of Calebin A is not likely to produce any significant toxic effects in male and female Wistar rats and no reproductive or developmental toxicity was observed at the same dose and hence Calebin A at 100 mg/kg was determined as “No Observed Adverse Effect Level (NOAEL)” under the test conditions.